Valorisation of Atlantic codfish (Gadus morhua) frames from the cure-salting industry as fish protein hydrolysates with in vitro bioactive properties - Rodrigues, Daniela P.; Calado, Ricardo; Ameixa, Olga M. C. C.; Valcárcel, J.; Vázquez, José Antonio (LWT, 2021)
8 pages, 7 tables, 3 figures The fishing industry is often targeted as a producer of organic streams with low economic value. Biotechnological approaches can play a crucial role in transforming and adding value to these streams for their further use and upcycle. In this study, Atlantic codfish (Gadus morhua) frames, were subjected to Alcalase hydrolysis, whose optimal conditions were first fine-tuned and established as follows: 56.8 °C, pH 8.35, [Alcalase] = 0.25% (v/w) and 3 h of hydrolysis. Subsequently, under these conditions, a set of 5 L-pH-stat reactor validated the optimization tests. Our results showed that fish protein hydrolysates (FPH) exhibited a high yield of digestion (>80%) and a remarkable high degree of hydrolysis (37%). A high content of soluble protein (66 g/L), with an amino acid profile with viability for food and nutraceutical applications and a near total in vitro digestibility (>92%) were revealed. Moreover, antioxidant and antihypertensive activities were also detected. The hydrolysates presented an average molecular weight of 1709 Da and a peptide size distribution of 49% below 1 kDa and 41% in the range of 1–3 kDa. These findings suggest that Alcalase hydrolysis has the potential to recover functional bio compounds from codfish frames, boosting the economy through green technology This research was funded by the project Xunta de Galicia (Grupos de Potential Crecimiento, IN607B 2018/19), CESAM and FCT, MCTES (UIDP/50017/2020+UIDB/50017/2020), through national funds and the project SUShI (CENTRO-01-0145-FEDER-030818) co-funded by Centro 2020 program, Portugal 2020, through the European Regional Development Fund, through the National Science Foundation (FCT, MCTES). D.P.R. is funded by a PhD grant attributed by FCT, MCTES (PD/BD/143093/2018). O.M.C.C.A. is funded by national funds (OE), through FCT, in the scope of the framework contract foreseen in the numbers 4, 5, and 6 of the article 23, of the Decree-Law 57/2016, of August 29, changed by Law 57/2017, of July 19 Peer ...